PRODUCT QUALITY AND PURCHASE INTENTION EFFECTS ON MARKETING PERFORMANCE: THE MEDIATING ROLE OF PURCHASE DECISIONS IN FOOD-PROCESSING MSMES 4.0 - Djoko Nusantoro; Yudi Nur Supriadi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of product quality and buying interest on marketing performance mediated by purchasing decisions in MSMEs 4.0 in the food processing sector in Sidoarjo. An explanatory quantitative approach was used with a cross-sectional design, involving 296 respondents selected through proportionate stratified random sampling technique. Data were collected using a Likert scale questionnaire (1–5) adapted from standardized instruments, then analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.0. The results showed that product quality had a positive and significant effect on purchase interest and purchase decisions, while buying interest was proven to be a partial mediating variable between product quality and purchase decision. Purchasing decisions directly affect the marketing performance of MSMEs. Predictive analysis through PLSpredict confirms that the model has high predictive relevance to consumer behavior in the digital marketing era. These findings confirm that strengthening product quality, followed by a digital marketing strategy based on consumer interaction, is an important determinant in increasing the competitiveness and sustainability of MSMEs 4.0 in the processed food sector. This research contributes to the empirical literature on technology-based marketing and provides strategic recommendations for the development of MSMEs in the digital economy era.